Effect of seepage conditions on the microstructural evolution of loess across north-west China - Lin Wang; Wen-Chieh Cheng; Wenle Hu; Shaojie Wen; Sen Shang (iScience, 2022)
Summary: Loess features metastable microstructure and is deemed susceptible to chemical contaminant permeation. However, studies on the loess permeability evolution under water and chemical environments are remarkably limited. In this study, the response of the loess to the water and sodium sulfate seepages was analyzed using the temporal relationship of cations concentration, X-ray diffraction and fluorescence (XRD and XRF), mercury intrusion porosimetry (MIP), and scanning electron microscope (SEM) tests. The permeability evolution characteristics were identified, and its underlying mechanisms were revealed from aspects of the diffuse double layer (DDL) theory and physiochemical actions. The discharge of Mg2+ and precipitation of calcium carbonate, referred also to as the dedolomitization, degraded the macro permeability when subjected to the water seepage test. The salt-induced swelling, induced by the intrusion of Na+ into the DDL, caused an increase in the micropore fraction under the sodium sulfate seepage test, thereby increasing the macro permeability.